Analysis of influencing factors of stimulated reservoir volume (SRV) and zipper fracturing simulation in shale oil reservoirs of Hu326 Well area. Issue 2 (March 2021) - Zhang, Kuangsheng; Xiao, Yang; Liu, Hanbin; Tang, Meirong; Zhang, Yanjun; Wang, Jianhui; Zhang, Liying; Chen, Mingxin
Abstract: Horizontal Well SRV of intensive stage and high–intensity for shale oil reservoirs of Hu326, which are different beddings and develop natural fractures locally, is conducive to the formation of complex fracture network with the intersection of main fractures, natural fractures, bedding fractures and other secondary fractures. At present, although there are systematic theories and methods for the study on the extension of hydraulic fracture after intersecting natural fractures and bedding planes, there is no quantitative research on specific parameters, and the research results are not applicable to actual exploitation. Based on the characteristics of shale oil reservoirs and combined with the theory of formation strength with weak surface, this article discusses the formation mechanism of fracture network of jimusar shale oil reservoir and improves the extension law of hydraulic fractures after intersecting with natural fractures and bedding planes. And taking the jimusar shale oil reservoir as the object, the extension law of hydraulic fracture is analysed and the geomechanical influencing factors and engineering control parameters of SRV are determined. The research results provide theoretical basis and parameter guidance for SRV of jimusar shale oil reservoir.